Landing strategies focusing on the control of tibial rotation in the initial contact period of one-leg forward hops - Chen, W.-L.; Chen, Y.-T.; Huang, S.-Y.; Yang, C.-Y.; Wu, C.-D.; Chang, C.-W. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Anterior cruciate ligament (ACL) reconstruction (ACLR) surgeries successfully restore anterior tibial translation but not tibial rotation. This study aimed to explore landing strategies focusing on the control of tibial rotation at landing when the ACL is most vulnerable. Three groups of male subjects (50 ACLRs, 26 basketball players, and 31 controls) participated in one-leg forward hop tests for determining the tibial rotatory landing strategies adopted during the initial landing phase. The differences in knee kinematics and muscle activities between internal and external tibial rotatory (ITR, ETR) landing strategies were examined. A higher proportion of basketball players (34.6%) were found to adopt ITR strategies (controls: 6.5%), exhibiting significantly greater hopping distance and knee strength. After adjusting for hopping distance, subjects adopting ITR strategies were found to hop faster with straighter knees at foot contact and with greater ITR and less knee adduction angular displacement during the initial landing phase. However, significantly greater angular displacement in knee flexion, greater medial hamstring activities, and greater co-contraction index of hamstrings and medial knee muscles were also found during initial landing. Our results support the importance of the recruitments of medial hamstrings or the local co-contraction in assisting the rotatory control of the knee during initial landing for avoiding ACL injuries.